INSTRUCTIONAL COMMUNICATION PROCESS IN DIFFERENTIATED INSTRUCTION-BASED LEARNING IN CAMBRIDGE CURRICULUM MATHEMATICS LESSONS FOR ELEMENTARY SCHOOLS - Stevany Eryna Retnaningrum; Maulina Pia Wulandari (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
Curriculum chosen by the school will affect the teaching and learning approach. However, to get good learning results, good communication is needed between the teacher and the students, especially if the teacher differentiated the students based on the level (advanced, on level, and slow learner). The aim of this research is to analyses the communication process carried out by teachers in implementing Differentiated Instruction (DI) in Cambridge curriculum in mathematics lessons for grade 5 elementary school. The research method involves interviews with 3 teachers and 5 students, direct observation in class, and study of documents such as Lesson Plan, student projects, and evaluation results. The results show that the teacher be the main facilitator. It requires in-depth knowledge and effective communication skills. Messages are delivered directly using the context of daily and real examples. Students are divided into three levels. That all three levels of students can receive the lesson well, judging from the grades and feedback. This shows the success of the instructional communication process implemented. Instructional communication here involves complex interactions between the source and communicants. This research provides in-depth insight into how instructional communication in the context of DI can be implemented in supporting the effectiveness of Mathematics learning in elementary schools.